PEREBUTAN DIVESTASI SAHAM NEWMONT NUSA TENGGARA (2008-2012) - , HAFID RAHARDJO; , Dr. Eric Hiariej, M.Phil ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fierce competition happened to obtain the divestiture shares in Newmont Nusa Tenggara (NNT). Central government and regional government who are supported by House of Representatives, are fighting each other to control 31% shares of NNT, the multinational corporation that operates in gold and copper mines. When central government agreed to purchase the remaining 7% of the shares from NNT, surprisingly, House of Representatives decide to report government action to Supreme Audit Agency and Constitutional Court. Both institutions ruled that government cannot continue the purchase without House approval as long as it financed by state budget. Government defeat in these terms became crucial point to analyze the relations between state and multinational corporation in the âreformasiâ era. Regional government effort to regulate their regions turns out became open confrontation with central government authority. Uniquely, House of Representatives is eager to help regional government to achieve their means. This situation proves that Newmont share ownership is having strategic value for all of the actors who fight for it. House of Representatives involvement in this matter strengthened that this case is not only about economics issue, but also political conflict. Moreover, regional government company partner who possessed 24% shares, owned by Aburizal Bakrie, chairman of Golkar political party. Golkar lawmakers in the House of Representatives, consistently question government decision regarding the purchase of Newmont shares. This paper intends to describe the conflict in chronological way, as well as to analyze the interest of all the actors who compete for the shares. Using theoretical approach from capitalist state concept, we get two main findings from this case. First, government policy to purchase NNT shares has exceeded the limit of relative autonomy in capitalist state. Second, Bakrie is enforcing subjective relations logic between state and capitalist, through Golkar constant intervention to invalidate government policy to purchase of NNT shares. Based on this case, we can analyze number of things, such as